Memandirikan Masyarakat Melalui Gerakan 1 Rumah 1 Jumantik (G1R1J) Serta Edukasi Gejala DBD di Kelurahan Bandengan - Jaya Maulana; Ristiawati; Nonik Eka Martyastuti (Jurnal Pengabdian Nasional (JPN) Indonesia, 2023)
The increase in dengue cases continues to occur, especially during the rainy season. The Ministry of Health noted that in 2022, the cumulative number of Dengue cases in Indonesia up to the 22nd week was reported as 45,387 cases and the number of deaths due to DHF reached 432 cases. Bandengan Village is one of the DHF endemic areas, data obtained from the Dukuh Health Center shows the number of cases of DHF cases as many as 2 cases in July 2022, this figure is the highest number in the working area of the Dukuh Health Center. This is exacerbated by the existing problems in the Bandengan sub-district, including the lack of community participation in efforts to prevent DHF and monitoring of larvae has not been carried out routinely. Methods This community service activity uses an extension and FGD approach. The activity was carried out for 3 hours with 30 participants consisting of cadres, youth leaders, community leaders, RW heads. There was an increase in the knowledge of 27 socialization participants from the post-test results, as well as the formation of the TOT team and the jumantik monitoring and evaluation team at the RW level which will disseminate knowledge and skills in dengue prevention through the 1 house 1 jumantik movement (G1R1J).